Ecological Risks of Heavy Metals and Microbiome Taxonomic Profile of a Freshwater Stream Receiving Wastewater of Textile Industry - Odubanjo, Grace Olunike; Oyetibo, Ganiyu Oladunjoye; Ilori, Matthew Olusoji (Frontiers in Environmental Science, 2021)
Textile wastewater (TWW) contains toxic metals that are inimical to microbiome, aesthetic quality, and the health of the receiving freshwater. TWW-impacted freshwater (L2) was assessed for metals eco-toxicity and the consequent impact on microbiome taxonomic profile (MTP) compared to a pristine environment (L1). The conductivity (1750 μS/cm), chemical oxygen demand (2,110 mg/L), biochemical oxygen demand (850 mg/L), and salinity (5,250 mg/L) of L2 were far above the permissible limits. Mercury posed very high ecological risks in the water column of L2 as lead, arsenic, and copper exerted high risk in the sediment. The MTP of L2 revealed the dominance of Euryarchaeota (48.6%) and Bathyarchaeota (45.9%) among the Archaea. The relative abundances of Proteobacteria and Bacteroidetes increased from 38.3 to 2.0%, respectively, in the L1 ecosystem to 42.1 and 12.9%, correspondingly, in L2. Unclassified Eukarya_uc_p (50.4%) and Fungi_uc (16.0%) were key players among the fungi kingdom in L2. The impact of the TWW on the microbiome was evident with the extinction of 6,249, 32,272, and 10,029 species of archaea, bacteria, and fungi, respectively. Whereas, 35,157, 32,394, and 7,291 species of archaea, bacteria, and fungi, correspondingly, exclusively found in L2 were assumed to be invading resident communities that combined with dominant autochthonous strains in shaping the ecophysiology dynamics in TWW-impacted freshwater. While the sensitive microorganisms in L2 are suggested bio-indicators of TWW ecotoxicity, the emergent and dominant taxa are pivotal to natural attenuation processes in the contaminated ecosystem that could be adopted for biotechnological strategy in decommissioning the TWW-impacted freshwater.